Current challenges in personalizing warfarin therapy. Issue 3 (May 2011) - McMillin, Gwendolyn A; Vazquez, Sara R; Pendleton, Robert C
In an exciting era where novel oral anticoagulants, such as the factor Xa and direct thrombin inhibitors, are beginning to emerge as therapeutic options, the vitamin K antagonists (VKAs) such as warfarin, which have been in clinical use for over half a century, will remain an important part of the therapeutic landscape for the foreseeable future. The optimal effectiveness and safety of the VKAs is limited by significant inter- and intra- patient variability in dose response. As such, routine laboratory monitoring with subsequent dose adjustment to achieve and maintain an international normalized ratio (INR) that falls within a narrow therapeutic range is necessary; even with frequent INR monitoring, time in therapeutic range of VKAs is generally <60% in usual care settings. Yet, personalized approaches to warfarin therapy, such as the routine incorporation of pharmacogenetic data into dose selection and adjustment, the selective use of prescribed doses of vitamin K for those patients with unstable INRs, and integration of patient self-testing /self-management, has the potential to improve the safety, efficacy and ease of use of warfarin. To date, no randomized trials have proven the benefits of routine pharmacogenetic testing for warfarin initiation; however, pivotal trials are ongoing. Through further investigative work, allowing these personalized strategies to realize their full potential, warfarin may remain a preferred therapeutic oral anticoagulant for years to come.